Binding of cyclic Di-AMP to the staphylococcus aureus sensor kinase KdpD occurs via the universal stress protein domain and downregulates the expression of the Kdp potassium transporter - Moscoso,JA; Schramke,H; Zhang,Y; Tosi,T; Dehbi,A; Jung,K; Gründling,A (Journal of Bacteriology, 2015)
Nucleotide signalling molecules are important intracellular messengers that regulate a wide range of biological functions. The human pathogen Staphylococcus aureus produces the signalling nucleotide cyclic di-adenosine monophosphate (c-di-AMP). This molecule is common among Gram-positive bacteria and in many organisms essential for survival under standard laboratory growth conditions. In this study, we investigated the interaction of c-di-AMP with the S. aureus KdpD protein. The sensor kinase KdpD forms a two-component signalling system with the response regulator KdpE and regulates the expression of the kdpDE genes and the kdpFABC operon coding for the Kdp potassium transporter components. Here, we show that the S. aureus KdpD protein binds c-di-AMP specifically and with an affinity in the micromolar range through its universal stress protein (USP) domain. This domain is located within the N-terminal cytoplasmic region of KdpD and amino acids of a conserved SxS-X20-FTAxY motif are important for this binding. We further show that KdpD2, a second KdpD protein found in some S. aureus strains, also binds c-di-AMP and our bioinformatics analysis indicates that a subclass of KdpD proteins in c-di-AMP-producing bacteria has evolved to bind this signalling nucleotide. Finally, we show that c-di-AMP binding to KdpD inhibits the up-regulation of the kdpFABC operon under salt stress, thus indicating that c-di-AMP is a negative regulator of potassium uptake in S. aureus. IMPORTANCE: Staphylococcus aureus is an important human pathogen and major cause of food poisoning in western countries. A common method for food preservation is the use of salt to drive dehydration. This study sheds light on the regulation of potassium uptake in Staphylococcus aureus, an important aspect of this bacterium's ability to tolerate high levels of salt. We show that the signalling nucleotide c-di-AMP binds to a regulatory component of the Kdp potassium uptake system and that this binding has an inh